The Influence of Health Education on Knowledge about Sleep Hygiene in the Elderly: A Quasi-Experimental Study - Lufthiani Anwar; Siti Zahara Nasution; Alfi Syahrin Siregar (Caring: Indonesian Journal of Nursing Science, 2026)
Sleep disturbances are common among older adults and are often associated with inadequate knowledge of sleep hygiene, resulting in poor sleep quality and reduced well-being. This study aimed to determine the effect of health education on knowledge regarding sleep hygiene among elderly individuals in Hamlet III, Selemak Village, Hamparan Perak Subdistrict, Deli Serdang Regency. A quasi-experimental study using a one-group pretest-posttest design was conducted among 40 elderly participants selected through total sampling. Data were collected using a structured questionnaire consisting of 20 items assessing sleep hygiene knowledge before and after intervention. The intervention consisted of one 45-minute health education session using lectures, discussion, and leaflet media. Data were analyzed using the Wilcoxon signed-rank test. Before intervention, knowledge levels were categorized as good (5%), fair (75%), and poor (20%). After intervention, good knowledge increased to 47.5%, while fair knowledge reached 52.5%. Median knowledge scores increased from 11 to 16. Statistical analysis showed a significant improvement after intervention (Z = -4.692; p < 0.001), with a large effect size (r = 0.74). Health education was effective in improving sleep hygiene knowledge among older adults. Routine educational programs are recommended to promote healthy sleep behaviors in the elderly. Keyword: Health education, Sleep hygiene, Elderly, Knowledge